2007
DOI: 10.1002/adfm.200600199
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity of a Low‐Bandgap Conjugated Polymer

Abstract: The photoconductive properties of a novel low‐bandgap conjugated polymer, poly[2,6‐(4,4‐bis‐(2‐ethylhexyl)‐4H‐cyclopenta[2,1‐b;3,4‐b′]dithiophene)‐alt‐4,7‐(2,1,3‐benzothiadiazole)], PCPDTBT, with an optical energy gap of Eg ∼ 1.5 eV, have been studied. The results of photoluminescence and photoconductivity measurements indicate efficient electron transfer from PCPDTBT to PCBM ([6,6]‐phenyl‐C61 butyric acid methyl ester, a fullerene derivative), where PCPDTBT acts as the electron donor and PCBM as the electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
236
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(246 citation statements)
references
References 17 publications
3
236
0
7
Order By: Relevance
“…5,[30][31][32][33][34][35][40][41][42][43] On this basis, when BT and TPD are assembled together in a repeating polymer unit, we expect that the energy levels of the polymer could be tailored to give a wide photo absorption range with alterations to the TPD moiety, resulting in changes to the HOMO energy level and changes in the BT unit, resulting in the alteration of the absorption at higher wavelengths. While new D-A units and their combinations have been investigated, improved molecular designs incorporating further combinations of D-A units are possible but have so far not been well-reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[30][31][32][33][34][35][40][41][42][43] On this basis, when BT and TPD are assembled together in a repeating polymer unit, we expect that the energy levels of the polymer could be tailored to give a wide photo absorption range with alterations to the TPD moiety, resulting in changes to the HOMO energy level and changes in the BT unit, resulting in the alteration of the absorption at higher wavelengths. While new D-A units and their combinations have been investigated, improved molecular designs incorporating further combinations of D-A units are possible but have so far not been well-reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Benzothiadiazole (BT) and its analogs have been used as electron acceptor groups in conjunction with various donor units such as cyclopentadithiophene (CPDT); compounds containing these acceptor groups exhibit lower-energy levels and a reduction in the band gap compared with other D-A alternating copolymers. [23][24][25][26][27][28][29] Since the development of poly [4,4- Figure 1), one of the first efficient third-generation donor-type conjugated polymers, [30][31][32][33][34][35] various new conjugated polymers applying D-A structures have been synthesized. These feature a lower-energy band gap to capture a wider range of the solar spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…NIR photodetectors are important in medical, industrial, communication, scientific and military applications as well as for night-vision imaging and security [14][15][16] . NIR-sensitive photodectectors have previously been demonstrated using inorganic quantum dot sensitization 17,18 , narrow optical-gap donor organic semiconductors within a conventional thin heterojunction structure 14,19,20 , and more recently by harvesting sub-gap charge transfer states (CT) 15,21,22 . Yang et al have reported on the use of CT state absorption to extend the spectral response of an OPD based on a P3HT:PC60BM blend to the NIR 22 .…”
mentioning
confidence: 99%
“…For an efficient solar cell, the HOMO and the LUMO energies of donors should be more positive than those of acceptors in order to guarantee a ready charge transfer in the device. [12] Therefore, [70]PCBM, with an experimentally determined LUMO level of À4.3 eV and a HOMO level of À6.1 eV, was chosen as acceptor. In the pair, a 0.9 eV offset of HOMO levels and a 1. annealing, the PBTT-based bulk-heterojunction solar cells show an overall conversion efficiency of 2.7 % under 1 sun light illumination.…”
Section: Resultsmentioning
confidence: 99%